HISTORICAL INFORMATICS: METHODOLOGICAL AND HISTORIOGRAPHICAL ASPECTS OF DEVELOPMENT - Saida Safibullayevna Beknazarova; Zamira Raimovna Ishanxadjayeva; Mustofoyeva Malika G’ayratjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
One of the main trends in the development of science in the last decades of the XX - early XXI centuries is the increasing role of information support for research, the widespread introduction of computer methods and information technologies into research practice. This trend is also evident in the humanities, primarily historical, with its reliance on the source base. Historians turned to the use of computer methods for analyzing information from historical sources already in the early 1960s, and since then this process has been developing, reflecting the realities of the rapidly changing information space. In the late 1980s and early 1990s, in the era of the "microcomputer revolution", historical computer science was formed as part of this process, which has now reached a new level of understanding the accumulated experience and assessing the prospects for development.